Evaluation of pitomba extract as a natural antioxidant in fresh sausages: Effects on physicochemical properties and lipid oxidation - Taline Fiorucci da Silva; Flávia Aparecida Reitz Cardoso; Nathália Leticia Hernandez Brito; Sahra Gadia Trelha; Stefanie Calisto Casarin; Leila Larisa Medeiros Marques; Adriana Aparecida Droval (Journal of Agriculture and Food Research)
This study evaluated the physical and chemical characteristics and lipid oxidation of fresh pork sausages containing pitomba extract as a substitute for synthetic antioxidants. Five formulations were prepared: a control sample (C) without antioxidants, a standard sample (A1) with 0.25 % sodium erythorbate, and three samples with pitomba extract at 0.25 % (A2), 0.50 % (A3), and 1.0 % (A4). Pitomba extract was obtained using a natural solvent composed of L-proline and levulinic acid, which effectively extracted phenolic compounds from the seeds. This method demonstrated strong antioxidant activity, surpassing traditional solvents, highlighting its potential as a natural alternative for bioactive compound extraction. The sausages were analyzed for pH, water holding capacity (WHC), cooking loss (CWL), lipid oxidation, and objective color (L∗, a∗, b∗, chroma, and hue angle). Analyses were conducted 24 h after production and again on days 7, 11, and 14 of refrigerated storage at 5 °C. The results revealed significant differences by the 14th day of storage (p˂0.05). The average pH ranged from 6.13 to 6.32, decreasing with higher concentrations of pitomba extract. WHC was lowest in the sample with 1.0 % extract (A4, 74.94 g 100 g−1), while CWL increased with extract concentration, reaching 15 g 100 g−1 in A4 compared to 7.92 g 100 g−1 in A1. Lipid oxidation remained low across all samples, ranging from 0.24 to 0.32 mg MDA kg−1 after 14 days, indicating good oxidative stability. Color analysis showed that samples with higher pitomba extract concentrations had intensified redness (a∗ value) and greater visual appeal. Sample A2 (with 0.25 % pitomba extract) exhibited color results (ΔE∗ = 21.53) closer to the standard sample A1 (ΔE∗ = 24.49), while A4 (ΔE∗ = 12.69) showed the most distinct color difference. These findings suggest that pitomba extract can effectively replace synthetic antioxidants in fresh pork sausages, improving product quality and shelf life. The sample with 0.25 % pitomba extract (A2) achieved results similar to the standard formulation, demonstrating its potential for industrial scalability as a natural and sustainable alternative.